Structures of greater good theodicies: The objection from alternative goods - Langtry, Bruce (Sophia, 1998)
The main issue in this paper has been whether appeal to greater goods can explain why God, if he exists, is justified in refraining from ensuring that there is little or no evil. I have argued that in principle it can. I have not defended the plausibility of the view that there actually are greater goods for whose sake God’s actions are planned; nor have I attempted to identify candidate goods performing the role envisaged. However those tasks form part of my larger project. Well beyond my reach is an item on my idle wish list: an explanation of why, assuming that God could have strongly actualized suitable alternative goods with less evil, he did not in fact do so.